2015
DOI: 10.1016/j.labeco.2015.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Guest workers in the underground economy

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Employers in Thailand spend long time in processing border-pass documents for migrant labors. Rules and regulations were therefore significant obstacles leading to construction delays as well as the case in Japan and Taiwan by the research of Djajić and Mesnard (2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Employers in Thailand spend long time in processing border-pass documents for migrant labors. Rules and regulations were therefore significant obstacles leading to construction delays as well as the case in Japan and Taiwan by the research of Djajić and Mesnard (2015).…”
Section: Discussionmentioning
confidence: 99%
“…Time-consuming migrant labor document ECAM 29,4 process in England significantly contributed to loss of migrant labor working time (Janta et al, 2011). In addition, the research conducted in Taiwan, Japan and South Korea countries found time-consumed and difficult authorization process in work permit were experienced by migrant worker (Djaji c and Mesnard, 2015). As a result, migrant labors avoided this document process.…”
Section: Migrant Labor Issues In Other Countriesmentioning
confidence: 99%
“…5 In contrast, the traditional European guest-worker programs, as in France and Germany, have differed from these TFW programs in the extent that guest workers have stayed in the receiving countries for much longer than originally expected. 6 Several theoretical studies have considered optimal guest-worker policy within this context, that TFWs often choose to stay beyond the time limit set for their visas; see for instance Djajić and Milbourne (1988), Epstein et al (1999), Djajić (2013) and Djajić and Mesnard (2015). Djajić et al (2012) consider the interaction between host country and receiving country policies with a focus on skilled migration.…”
Section: Introductionmentioning
confidence: 99%
“…Several theoretical studies have considered optimal guest‐worker policy within this context, that TFWs often choose to stay beyond the time limit set for their visas; see for instance Djajić and Milbourne (), Epstein et al. (), Djajić () and Djajić and Mesnard (). Djajić et al.…”
Section: Introductionmentioning
confidence: 99%
“…More recent papers by Friebel and Guriev (2006), Djaji¢ (2013), Djaji¢ and Mesnard (2013) and Djaji¢ and Vinogradova (2013), allow for the possibility of deportation after a successful entry, although this is modeled deterministically and the option of voluntary return is not considered.…”
Section: Introductionmentioning
confidence: 99%